Performance de diferentes substratos em sistemas de wetlands construídos no tratamento de efluente sintético em condições subtropicais - Lima, Mateus Xavier de (2018)
Constructed wetlands (CW) filled with gravel (CW-G and CW-GP), light expanded clay (CW-C and CW-CP), clay bricks (CW-B and CW-BP) and one with floating Eichhornia crassipes (CW-FM) were evaluated in the treatment of synthetic wastewater simulating sanitary sewage in batch mode with cycles of 48 h-48 h-72 h. Temperature, pH, dissolved oxygen, oxidation-reduction potential, total alkalinity, total volatile acids, acetylsalicylic acid (ASA), chemical oxygen demand (COD), total Kjeldahl nitrogen (TKN), ammonia nitrogen (TAN) and total phosphorus (TP) were determined in influent and effluent samples. Organic matter degradation was evaluated through first-order models adjusted to experimental data. Phosphorus adsorption and desorption in bricks were determined. Total nitrogen (TN) and total phosphorus (TP) content were determined in the dry biomass of plants from the vegetated systems. The best overall performance was observed in CW-BP, with removals of 8.84 gCOD m-2 , 1.92 gTKN m-2 , 0.37 gNATm-2 , 0.98 gTP m-2 and 92% of ASA. The model presented by Brasil et al. (2007) best adjusted to COD experimental data, specially in CW-CP (kB 1,61 d-1; n 0,35; R2 0,992) and the pseudo-first and pseudo-second order models to phosphorus adsorption kinetics data (R2 0.98). Langmuir and Freundlich isotherms adjusted to experimental data (R2 0.99) with maximum adsorption of 2.27 mgP g -1 and fm of 0.853, indicating high phosphorus retention capacity in bricks. The biomass from CW-FM presented the major nitrogen and phosphorus content, 17.13 g and 10.54 g, respectively, at the end of the experimental period.